Muscle spindles provide servo-assistance to jaw-closing muscles for chewing hard foods - Hossain, Mohammad Zakir; Kitagawa, J.; Razak, Fathilah Abdul; Bakri, M.M. (Penerbit Universiti Kebangsaan Malaysia, 2015)
The fundamental pattern of chewing induced by the network of neurons called central pattern generator has been reported to be modified by the information arising from the various oro-facial sensory receptors including muscle spindles of jaw closing muscles. The cell bodies of primary afferent neurons from these muscle spindles lie in mesencephalic trigeminal nucleus (MTN) in the brainstem. The aim of the study was to understand whether muscle spindles from jaw-closing muscles play any role in hard food chewing. Single neuronal discharge of muscle spindle afferents was recorded from the MTN simultaneous with jaw-movement and electromyograpic (EMG) activities of the left masseter (jaw-closing) muscle during chewing soft and hard foods (apple and pellet) in awake rabbits. Ten consecutive chewing cycles were taken for analysis. Discharge of nineteen muscle spindles from seven rabbits was successfully recorded. Muscle-spindle discharge was significantly higher during the closing phase of jaw-movement for the hard food chewing than for the soft food. The jaw-closing muscle EMG activity was significantly higher during hard food chewing compared to soft food. The spindle discharge was higher when the masseter muscle activity was greater for chewing hard food. Significant positive (r=0.822, p=<0.001) correlation was found between the difference of muscle activity between apple and pellet and the difference of spindle discharge between apple and pellet. Above findings suggest that the increase of spindle discharge during hard food chewing may play a role for facilitating jaw-closing muscle activities and thereby provides servo-assistance to jaw-closing muscles to compensate the hardness of food.